Magnetic properties of quasi-one-dimensional antiferromagnets (Y1−xNdx)2BaNiO5 (x=1, 0.15) - Popova, Elena; Klimin, S. A.; Popova, M. N.; Klingeler, Rüdiger; Tristan, N.; Büchner, B.; Vasiliev, A. N. (Journal of magnetism and magnetic materials, 2013)
We present the magnetic properties of (Y1−xNdx)2BaNiO5 (x=1, 0.15) investigated by means of specific heat, magnetic susceptibility, and spectroscopic measurements. Magnetic ordering occurs at 47K and 13K in the compounds with x=1 and x=0.15, respectively. We estimate the magnetic contribution of the neodymium subsystem to magnetization and specific heat using temperature dependences of the splitting of ground Kramers doublet of Nd3+ ion obtained from spectroscopic experiment. We show that both Nd-Ni and Nd-Nd interactions should be taken into account. An origin of the observed spin-glass state below ∼5K and a contribution of the Ni chain breaks to the magnetization and specific heat are discussed.
Im Text ist "1−x", "x", "2" und "5" tiefgestellt
Available online 27 November 2012
Gesehen am 05.01.2022